Pengaruh Perencanaan Pajak Dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahaan Perbankan Swasta yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020 - Mike Kusuma Dewi; Fatihah Aulia Rahmi (JURNAL PUNDI, 2022)
This study is entitled The Effect of Tax Planning and Company Size on Earnings Management in Private Banking Companies Listed on the Indonesia Stock Exchange in 2018-2020. The formulation of the problem in this study is how the effect of tax planning and company size on earnings management. This study aims to analyze empirically the effect of tax planning and firm size on earnings management. The population in this study are private banking companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The method of determining the sample in this study used the purposive sampling method, and based on the specified criteria, the number of samples was 27 companies. The data source in this study is secondary data obtained from the annual financial statements of companies listed on the Indonesia Stock Exchange for the 2018-2020 period by accessing www.idx.co.id. The analytical technique used is multiple linear regression analysis with Eviews application tools. The results of this study indicate that tax planning has no effect on earnings management, and firm size has a positive effect on earnings management.